Kontribusi Keagenan Kapal Terhadap Pencegahan Pencemaran Laut Di PT Internasional Total Service & Logistics - Rochmansyah, Rizal; Rosnani, Rosnani; Pratama, Robby (Jurnal Cakrawala Bahari, 2025)
Marine pollution has become one of the most critical environmental issues in the maritime sector. This study aims to analyze the contribution of ship agencies in preventing marine pollution at PT Internasional Total Service & Logistics (ITL), particularly in Cigading Port, Banten. A qualitative descriptive approach was employed to explore the administrative, operational, and educational roles of ship agents in environmental management. Data were collected through in-depth interviews, participatory observations, and document analysis, followed by an interactive analysis model by Miles, Huberman, and Saldaña. The results show that ship agents play a crucial role in ensuring compliance with MARPOL 73/78 regulations. Out of ten ships served in the first quarter of 2024, 100% submitted mandatory environmental documents, while 90% ensured conformity with the Shipboard Oil Pollution Emergency Plan (SOPEP). Operationally, from seven bunkering activities observed, no oil spills were recorded, and 85.7% of sludge oil disposal was carried out through licensed waste management companies. Moreover, four environmental awareness programs were conducted, with 78% of participants reporting improved understanding of marine environmental protection. The overall contribution of ship agencies is categorized as very good, with an effectiveness rate of 89%. These findings indicate that ship agencies have a significant and strategic role in supporting sustainable maritime operations by implementing administrative control, operational monitoring, and environmental education. Strengthening collaboration between ship agents, port authorities, and environmental institutions is recommended to enhance the effectiveness of marine pollution prevention in Indonesian ports.